2022
DOI: 10.3390/ijerph19169947
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 Gene Expression and Protein Level Changes Observed in Response to Wingate Anaerobic Test in High-Trained Athletes and Non-Trained Controls

Abstract: Intensive, acute exercise may bring a large systemic inflammatory response marked by substantial increases in inflammatory cytokines and chemokines. One such chemokines–CCL2–is a key factor involved in inflammatory reaction to exercise. The direct aim of the study was to describe the changes in the CCL2 expression levels after anaerobic exercise in well-trained athletes adapted to long-term training and in non-trained participants. The expression of CCL2 mRNA was evaluated in peripheral blood MNCs and CCL2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In non-training subjects, the results were different. The number of MCP-1 transcripts was relatively high immediately after the test, and then the observed MCP-1 expression decreased to a lower level [ 75 ]. Also, when running on a treadmill for 45 and 60 min with VO2max = 60% or 80%, significant increases in this cytokine level were found in the plasma of trained male runners [ 66 ].…”
Section: Cytokines In Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In non-training subjects, the results were different. The number of MCP-1 transcripts was relatively high immediately after the test, and then the observed MCP-1 expression decreased to a lower level [ 75 ]. Also, when running on a treadmill for 45 and 60 min with VO2max = 60% or 80%, significant increases in this cytokine level were found in the plasma of trained male runners [ 66 ].…”
Section: Cytokines In Physical Activitymentioning
confidence: 99%
“…Only a few studies have examined the relationship between training level and cytokine secretion. For example, one study found that trained athletes had lower levels of chemokine CCL2 compared to non-trained individuals, indicating a potential adaptation to chronic exercise [ 75 ]. Another study found that trained athletes had lesser magnitude of change in the cytokine levels (IL-6 and TNF-α), during strenuous exercise compared to untrained individuals [ 113 ].…”
Section: Effect Of Training Level On the Amount Of Secreted Cytokinesmentioning
confidence: 99%